2007
DOI: 10.1007/s11920-007-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of bipolar disorder

Abstract: Bipolar disorder is a mood disorder characterized by impairing episodes of mania and depression. Twin studies have established that bipolar disorder is among the most heritable of medical disorders and efforts to identify specific susceptibility genes have intensified over the past two decades. The search for genes influencing bipolar disorder has been complicated by a paucity of animal models, limited understanding of pathogenesis, and the genetic and phenotypic complexity of the syndrome. Linkage studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 132 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…Candidate gene studies have provided tantalizing glimpses into the possible genetic aetiology of BPD but few, if any genes are universally accepted (Smoller and Gardner-Schuster, 2007, Burmeister et al, 2008). Of those genes which have been reasonably well-studied, many are putative candidates because of their central role in neurotransmitter pathways, particularly the dopamine, serotonin and glutamate systems.…”
Section: Molecular Genetic Studies Of Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate gene studies have provided tantalizing glimpses into the possible genetic aetiology of BPD but few, if any genes are universally accepted (Smoller and Gardner-Schuster, 2007, Burmeister et al, 2008). Of those genes which have been reasonably well-studied, many are putative candidates because of their central role in neurotransmitter pathways, particularly the dopamine, serotonin and glutamate systems.…”
Section: Molecular Genetic Studies Of Bpdmentioning
confidence: 99%
“…Increased rates of schizophrenia are seen among relatives of people with BPD (Valles et al, 2000, Mortensen et al, 2003), and increased risk for schizoaffective disorder is found among relatives of both schizophrenia and bipolar patients (Kendler and Gardner, 1997, Cardno et al, 2002, Mortensen et al, 2003). Several authors have highlighted regions which have shown linkage to both BPD and schizophrenia, including 6q21–25, 10p14, 13q32–34, 18p11 and 22q11–13 (Berrettini, 2000, Bramon and Sham, 2001, Smoller and Gardner-Schuster, 2007) although it is possible that these shared peaks are due to entirely separate genes, or indeed, just coincidence (Kendler, 2006). Similarly, several candidate genes have been associated with both schizophrenia and bipolar diagnoses (e.g.…”
Section: Genetics and The Definition Of Bipolar Disordermentioning
confidence: 99%
“…As both disorders are thought to have relatively high heritability (~80%) [3, 4], biomarkers tied to specific candidate genes have often formed the basis for these pursuits. For example, both schizophrenia and bipolar disorder have been the subject of hundreds of candidate-gene association analyses [57] and, most recently, a handful of genome-wide association studies [814]. Through meta-analysis, our group and others have identified several genetic polymorphisms that influence the risk for one or the other disorder [6, 1521].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, psychotic BPD and early-onset BPD have been shown to be familial and heritable subtypes that may reflect more genetically homogeneous influences [Smoller and Gardner-Schuster, 2007]. Early-onset BPD was defined as having a first manic or depressive episode before age 18, and psychosis was defined as having had psychotic symptoms or a psychotic diagnosis on any of the STEP-BD instruments that assessed psychosis.…”
Section: Resultsmentioning
confidence: 99%